2012
DOI: 10.4103/2152-7806.103886
|View full text |Cite
|
Sign up to set email alerts
|

Age limit for surgical treatment of poor-grade patients with subarachnoid hemorrhage: A project of the Chugoku-Shikoku division of the Japan neurosurgical society

Abstract: Objective:Management of elderly patients with poor-grade subarachnoid hemorrhage (SAH) remains controversial. The objective of this study was to investigate whether there is an age-dependent difference in the outcome of poor-grade SAH after surgical obliteration of the aneurysm.Methods:Data were reviewed retrospectively for 156 patients with poor-grade aneurysmal SAH at multiple centers in Chugoku and Shikoku, Japan. Patients were divided into age groups of 65-74 and ≥75 years old. Factors influencing a favora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Future work will be directed towards elucidating the mechanisms of neurological improvement upon relatively delayed ROCK inhibition after a CC lesion and determine whether they overlap with previously demonstrated effects in other forms of central nervous system injury, such as reduced inflammation, blood-brain barrier disruption, and glial scar formation, and enhanced axonal sprouting, neurogenesis, and remyelination. Given that fasudil is already in clinical use in the Far East, 38 clinical translation of our findings might be swift, if confirmed independently.…”
Section: Discussionsupporting
confidence: 53%
“…Future work will be directed towards elucidating the mechanisms of neurological improvement upon relatively delayed ROCK inhibition after a CC lesion and determine whether they overlap with previously demonstrated effects in other forms of central nervous system injury, such as reduced inflammation, blood-brain barrier disruption, and glial scar formation, and enhanced axonal sprouting, neurogenesis, and remyelination. Given that fasudil is already in clinical use in the Far East, 38 clinical translation of our findings might be swift, if confirmed independently.…”
Section: Discussionsupporting
confidence: 53%
“…This finding is similar to early studies. 35–37 40 IVH was significantly associated with poor outcome. IVH may probably cause irreversible periventricular brain damage.…”
Section: Discussionmentioning
confidence: 90%
“…This was due to the fact that several studies have indicated that clinical outcome was significantly different when the cut-off age was set at 75 years. 8 10) There have been no studies showing an age lower than 75 year old could be a cut-off point. We believe that 75 years of age should be considered “elderly” for aSAH when proper treatment is discussed in order to improve outcome.…”
Section: Discussionmentioning
confidence: 99%
“… 4 7) In particular, several studies indicat that poor outcome significantly increases in the patients over age 75. 8 10) …”
Section: Introductionmentioning
confidence: 99%